Resisting the 19th Century Colonial Politics of Exile: The Study of Kiai Ahmad Arrifai Kalisalak and Kiai Hasan Maolani Kuningan Letters - M. Adib Misbachul Islam; Muhammad Nida Fadlan; Abdullah Abdullah (Wawasan: Jurnal Ilmiah Agama dan Sosial Budaya, 2021)
This article aims to reveal the discourse on the resistance of two Javanese ulama who were victims of the Dutch colonial politics of exile in the 19th Century. This study uses several letter manuscripts written by Kiai Ahmad Arrifai Kalisalak and Kiai Hasan Maolani Kuningan from their exile as primary sources. The letters addressed to his family and followers in Java were written in Javanese with the Pegon script. Through historical studies and discourse analysis, this study finds that the Dutch colonial politics of exile was not able to dampen the resistance of the ulama. The writing of letters from exile by Kiai Ahmad Arrifai Kalisalak and Kiai Hasan Maolani was intended to compete with the colonial powers, producing heretical discourses and disturbing public order as a pretext to banish them. Thus, this article concludes that the two ulama did from their exile was a new mode of resistance against colonialism.